Development of Mangrove Forest Areas as a Central Area for Coastal Ecosystem Restoration and Development (PRPEP) and Tourist Attractions in Silo Baru Village, Silau Laut District, Asahan Regency - Abdul Azis Harahap; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the Development of Mangrove Forest Areas as a Central Area for Coastal Ecosystem Restoration and Development (PRPEP) and tourist attractions in Silo Baru Village, Silau Laut District, Asahan Regency. This study uses a qualitative approach, which aims to understand the phenomenon of mangrove forest area development in Silo Baru Village. This type of research is qualitative descriptive, which focuses on the presentation of conditions, strategies, and impacts of mangrove forest area development. The location of the research is Silo Baru Village, Silau Laut District, Asahan Regency, North Sumatra. Data Analysis Techniques The data that has been collected is analyzed using thematic analysis methods. Data collection techniques such as interviews, participatory observations, and documentation will provide a comprehensive picture of social interaction, community participation, and the challenges and development potential of the region. The results of the PRPEP Development research in Silo Baru Village have succeeded in restoring the mangrove ecosystem that was previously degraded. Restoration efforts through mangrove replanting, coastal land rehabilitation, and sustainable ecosystem management contribute to the restoration of biodiversity, including the return of typical flora and fauna species in coastal areas. The development of mangrove areas as ecotourism destinations also has a significant economic impact on the local community. Through ecotourism, people get new income opportunities from various sectors, such as tour guide services, homestay management, food stalls, and souvenir sales